America's best breakfasts : favorite local recipes from coast to coast - Schrager, Lee; Sussman, Adeena (Clarkson Potter/Publishers, 2016)
"Rise and dine! If there's one meal of the day to get passionate about--no matter where you're from in this great land--it's breakfast with all the fixings. Featuring down-home diners, iconic establishments, and the newest local hot spots, America's Best Breakfasts is a celebration of two of this nation's honored traditions: hitting the open road and enjoying an endless variety of breakfasts. Even without a road trip, you can re-create favorites that will satisfy any time of day,"--Amazon.com.